PERANCANGAN DENGAN MENGGUNAKAN METODE REVERSE ENGINEERING DAN VDI 2221 PADA PRODUK MEJA BELAJAR MULTIFUNGSI - Hery; Adianto; Daywin, Frans Jusuf (Universitas Tarumanagara, 2023)
The boarding house is an option for students or university students who study or go to school outside the city, far from their parents. The owners of boarding houses for rent will provide a study table in each room for the tenants to meet their needs. However, most of the study tables provided are less practical and less ergonomic, which will result in tenants lacking space to carry out other activities. Therefore, in this research, a redesign of multifunctional study table products available on the market was carried out using the reverse engineering method and VDI 2221. This research was carried out to design a study table that can solve the above problem, namely a study table that has several additional features to this product such as adding a multifunctional mattress feature that can be used as a sofa which will save space, adding a feature for placing the printer at the bottom of the table which will help the product's practicality in carrying out printing activities, adding a cool fan feature to the product This adds a double table feature to the study table, where one table is for placing a monitor and on the other table there is a cool fan for placing a laptop with a mattress as a seat. This research will be carried out using a questionnaire to determine people's needs and benchmark multifunctional study tables currently on the market to determine the size and features of competing products and adapt them to the product that will be redesigned.